Analisis Pembangunan Dan Dampak Ekonomi, lingkungan, Sosial, Budaya Masyarakat sekitar kawasan Destinasi Wisata Kolam Renang Kampung Bambu Kabupaten Bandung - Aisyah Nurfadilah, Siti; Ramdani, Dadan (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of the development of the Kampung Bambu Swimming Pool tourist destination in Bandung Regency on the surrounding community, from an economic, environmental, social, and cultural perspective. Using a qualitative approach through observation and in-depth interviews, this study found that the tourist destination has made a positive contribution, particularly in strengthening social interactions and creating alternative recreational spaces for the local community. Economically, although its impact is not significant, this tourism still contributes to the local economy through MSME activities and local consumption. Environmentally, cleanliness management remains a challenge, but overall, the community and visitors demonstrate an awareness of the importance of environmental protection. This study also emphasizes the importance of a participatory approach in managing community-based tourist destinations. The results of this study are expected to serve as a reference in formulating policies for more inclusive and sustainable local tourism development.